PENGARUH PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM TERHADAP AKHLAQ SISWA DI SEKOLAH DASAR MUHAMMADIYAH 3 DENPASAR BALI - Choliludin; Muhtadi; Adibah Jauhari (Arsy : Jurnal Studi Islam, 2020)
In the education sector, a culture of violence and deterioration in morals has been felt lately, many students are considered lacking in politeness both at school, at home and in the community.Humans in modern times and technological advances are now heavilyinfluenced by material souls, so that the pleasure of material is the ultimate goal of humans. In this case many people forget the moral norms. Religion has an important role in human life, because religion is the motivation of life and life and is a very important tool for self-control. Therefore the importance of Islamic religious education in life and human life both within the school, home (family) and society, then religious education must be carried out to create a healthy atmosphere of Islamic life, so in order to achieve this goal a child (student) cannot apart from the interference of various parties, especially families (parents), teachers and the community.Islamic religious education teachers are educators who carry out guidance, teaching and / or training activities consciously to their students to achieve the objectives of Islamic religious educationThis study aims to find out how the professionalism of the teacher of Islamic Education in Muhammadiyah 3 Elementary School Denpasar, how the students' behavior in Muhammadiyah 3 Elementary School Denpasar, and how much influence the professionalism of the teacher of Islamic Education on the morality of students in SD Muhammadiyah 3 Denpasar. This study uses quantitative research methods whose descriptions are in the form of numbers.The sample used was 100 respondents from class IV, V, VI SD Muhammadiyah 3 Denpasar.Based on the hypothesis test, it can be seen that Ha is accepted or there is a significant influence on professionalism of the students of SD Muhammadiyah 3 Denpasar. Based on the results of this study, the authors advise all teachers inMuhammadiyah 3 Elementary School Denpasar should the efforts made in improving professionalism continue to be warned so that educational goals can be achieved well so that the quality of religious education I increases.